The Lecture as Experiential Education: The Cucumber in 17th-Century Flemish Art. (June 2016) - Blenkinsop, Sean; Nolan, Carrie; Hunt, Jasper; Stonehouse, Paul; Telford, John
This article uses an unconventional format to problematize a common dichotomy found in the theory and practice of experiential education. The article comprises the contributions of five authors and begins with one author's description of a potential real-life scenario that provokes the question of whether an art history lecture might be understood as experiential education. Three of the remaining coauthors respond individually and independently to this question, and the final author joins with the first in the concluding comments section. The key consensus of the responding coauthors is that simplistically equating the Deweyan notion of primary experience with physical, tactile activity is a limited and limiting understanding of experience in education and that in fact, under the correct circumstances, a lecture can and even should be part of experiential education. Beyond this, the authors encourage educators to think carefully about the educational trajectory and contextual histories of the learners with whom they work. Finally, the two authors of the concluding comments suggest that the field, to do justice to the educational possibilities of all experiences, must begin to move beyond John Dewey while finding ways to overcome the deeply entrenched dualistic concept of experience that continues to affect our practices and theorizing.